Housing Commons: Alternatives to Housing Through Urban Commoning - Valiantzas, Zacharias; Arvanitidis, Paschalis (Sens public, 2024)
The paper builds upon the concepts of the right to the city and urban commoning, to advance the theory of housing commons. Moreover, it draws on selected initiatives to highlight commonalities and differences, and to portray the diversity of contemporary housing commons. We articulate the framework of urban commoning that urban commoners proclaim through Lefebvre’s (1968) right to the city, i.e., urban dwellers’ collective right and power over urban qualities and the urbanization processes. This has been embraced by the new social urban movements to deploy a range of actions and organizational forms, referred to as urban commoning for housing provision and the production of “common” built space, which are in conflict to neoliberal policies and the new urban enclosures. Along these lines the paper lays down a framework for understanding and analyzing housing commons as a social institution with social rights and responsibilities, founded on the principles of self-organization, de-commodification, social support and solidarity. On the empirical front, the paper analyses different (in spatial, political, organizational terms) cases of successful housing commons worldwide, to access their characteristics along the aforementioned principles. The paper concludes that in the present times, where housing problems and homelessness intensify, housing commons comprise not simply a mosaic of viable solutions, but a different mode of urban living imbued by the values of collectiveness, self-organization and solidarity.